Impact of E-Commerce in Indian Scenario: Exploring the Impact of E-Commerce on Indian Economy and Marketing Strategies (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The said research paper focuses on the impact of Electronic Commerce in India in the recent times. The process of conducting business transactions over the internet is known as E-Commerce. Experts have opined that a revolution has entered the information age which is similar to the industrial revolution. As a result of this, there haS been a large number of changes in the social, economic and cultural domains. One of the aspects of this revolution is changes in economic relations between individuals, corporations and governments. The combination of Business and Electronic Commerce will bring out a renaissance in the marketing world. This provides opportunities for the business to get closer to the customers by bringing them inside the company, thereby exploring the new product ideas which results in the customers’ involvement directly in the business.